'Gifts for the gods': lake-dwellers' macabre remedies against floods in the Central European Bronze Age. (1st June 2014) - Menotti, Francesco; Jennings, Benjamin; Gollnisch-Moos, Hartmut
Abstract : The lake-dwellings of the Circum-Alpine region have long been a rich source of detailed information about daily life in Bronze Age Europe, but their location made them vulnerable to changes in climate and lake level. At several Late Bronze Age examples, skulls of children were found at the edge of the lake settlement, close to the encircling palisade. Several of the children had suffered violent deaths, through blows to the head from axes or blunt instruments. They do not appear to have been human sacrifices, but the skulls may nonetheless have been offerings to the gods by communities faced with the threat of environmental change.